Physical characteristics and physical fitness in Norwegian junior elite team handball players. A cross-sectional study - Aalkjær, C. (Department of Sports Medicine, Norwegian School of Sport Sciences, 2018)
Purpose: Modern elite team handball is an intermittent sport characterized by technical and tactical skills, psychosocial behavior, physical characteristics and physical demands. The aim of the study was to examine physical characteristics and physical fitness in Norwegian junior elite team handball players, and compare players attending private elite sport high schools (NTG) with players attending regular public high schools (non-NTG). Further, we aimed to follow and monitor physical characteristics, fitness and patterns of injuries in a smaller study sample throughout season 2017/18. Methods: Body composition was measured in 49 NTG players (14 males and 35 females), and 44 non-NTG players (12 males and 32 females) using bioelectrical impedance analysis (InBody 720, Biospace, Seoul, Korea). In addition, physical fitness was measured in 10- and 20-meter sprint, countermovement jump, T-test agility, Yo-Yo intermittent recovery test level 1 and one repetition maximum in squat and bench press. Training hours/week, sleeping hours/night in weekdays and weekends, and injury patterns were recorded through self-conducted questionnaires.